2021
DOI: 10.1101/2021.08.11.21261918
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Exposome and its Associations with Broad Mental and Physical Health Measures in Early Adolescence

Abstract: Environment is key to human development, yet the complex network structure of exposures (i.e., exposome) makes it challenging to investigate. Here, we analyzed data from the Adolescent Brain and Cognitive Development (ABCD) Study , a large, diverse sample of US adolescents (N=11,235, mean age=10.9, 52% male) with phenotyping at multiple levels of environmental exposure. Applying data-driven iterative factor analyses and bifactor modeling, we reduced dimensionality from hundreds of exposures to six exposome sub… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 93 publications
(146 reference statements)
0
14
0
Order By: Relevance
“…To capture the exposome in early adolescence, we recently applied an approach using dimensionality reduction and bifactor modeling of the exposome in 2 youth cohorts (the Philadelphia Neurodevelopmental Cohort [PNC] and the Adolescent Brain Cognitive Development [ABCD] Study), showing that such an approach indeed facilitates generalizability across cohorts ( 49 ). Briefly, we combed through each cohort’s data and reduced dimensionality of all environmental exposures (798 exposures in the ABCD Study and 29 exposures in PNC) to a limited set of correlated environmental factor scores that capture different levels of exposure (e.g., household, neighborhood).…”
Section: The Potential Of a Data-driven Approach To Capture The Exposomementioning
confidence: 99%
See 1 more Smart Citation
“…To capture the exposome in early adolescence, we recently applied an approach using dimensionality reduction and bifactor modeling of the exposome in 2 youth cohorts (the Philadelphia Neurodevelopmental Cohort [PNC] and the Adolescent Brain Cognitive Development [ABCD] Study), showing that such an approach indeed facilitates generalizability across cohorts ( 49 ). Briefly, we combed through each cohort’s data and reduced dimensionality of all environmental exposures (798 exposures in the ABCD Study and 29 exposures in PNC) to a limited set of correlated environmental factor scores that capture different levels of exposure (e.g., household, neighborhood).…”
Section: The Potential Of a Data-driven Approach To Capture The Exposomementioning
confidence: 99%
“…The general ES receives loadings from all environmental exposures included in the model and therefore represents a weighted sum of multilevel environmental exposures for each study participant. After calculating the general exposome factor in the 2 independent datasets, we have shown that the general ES is associated with youth mental and general health measures in an almost identical magnitude (i.e., effect size), despite the fact that ABCD Study and PNC data were collected in different places and at different times with substantial differences in environmental phenotyping ( 49 ). We suggest that this general ES can potentially be useful because it captures a latent environment factor that is less likely to be skewed by a specific environmental exposure and might allow for better generalization of environment modeling across different cohorts, which is often very different.…”
Section: The Potential Of a Data-driven Approach To Capture The Exposomementioning
confidence: 99%
“…Psychosis spectrum disorder (PSD) has a complex, multifaceted, interconnected environmental etiology including exposures from different levels (e.g., family-, household-, neighborhood-, and state-level) ( 1 , 2 ). Evidence highlights the role of various environmental exposures such as pre- and perinatal complications, childhood adversities (e.g., abuse, neglect, nonintentional adversities), minority status, cannabis use, and urbanicity ( 3 , 4 ).…”
mentioning
confidence: 99%
“…Furthermore, not only significant life events but also day-to-day experiences play an important role ( 1 , 12 , 13 , 14 ). The environment in which a child grows up, including factors such as family, neighborhood, state, or country, can influence their development and psychopathology ( 1 , 2 , 15 , 16 ). Furthermore, environmental exposures do not occur in isolation.…”
mentioning
confidence: 99%
See 1 more Smart Citation